PENGARUH PELAKSANAAN FULL DAY SCHOOL TERHADAP HASIL SISWA KELAS XII DI SMA NEGERI 1 SUNGAI APIT BELAJAR - Festi Abdiyati; Zahirman Zahirman; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the implementation of full day school on the learning outcomes of class XII students at SMA Negeri 1 Sungai Apit. State high school 1 Sungai Apit students feel bored, saturated, when doing full day school activities because a day at school. The formulation of the problem in this research is” is there any the effect of implementation full day school on the learning outcomes of class XII students at SMA Negeri 1 Sungai Apit ?”. This study aims to know the effect of implementation on the learning outcomes of class XII student at SMA Negeri 1 Sungai Apit. This research was conducted at SMA Negeri 1 Sungai Apit, Sungai Apit sub_ district of Siak regency. This research was carried out in july until aguust 2019. This research uses a quantitative approach. Data collection techniques observation, questionnaires, intwerviews, and documentation. Based on the results of research conducted there is a negative influence in carrying out full day shool on the learning outcomes of class XII students at SMA Negeri 1Sungai Api. This can be seen from into the suffient the 60-73 which is included in the category enough.Key Words: Full Day School, Learning Outcomes